Top Five Physical Design Factors Contributing to Fall Initiation. (October 2018) - Pati, Debajyoti; Lee, Jaehoon; Mihandoust, Sahar; Kazem-Zadeh, Mahshad; Oh, Youngha
Purpose: To develop a prioritized list of physical design questions/interventions to reduce patient falls by conducting expanded analysis (Phase II) of data generated from a completed study phase. Background: Patient falls continue to be a critical concern for healthcare providers, patients, and families. While substantial literature exist on intrinsic factors, scientific evidence on the role of the physical environment is scarce. Method: Expanded analysis of data from 180 videos of trials conducted in a physical mock-up of a medical–surgical inpatient room in a previously completed study phase. The odds of subject's exhibited postures (predictors) on fall initiation (outcome) were examined in a series of generalized linear mixed effects models. Physical design elements and attributes associated with postures exhibiting statistical significance were examined. Results: Turning, pulling, pushing, and bending forward exhibited the highest odds of contributing to fall initiation in the bathroom. Grabbing, pushing, and sitting exhibited the highest odds of contributing to fall initiation around the patient bed. Physical design elements/attributes associated with the above postures are the (1) bathroom door; (2) bathroom spatial configuration—relative locations of door, toilet bowl, and the sink; (3) door, toilet, and sink hardware; (4) space availability/tightness inside the clinician zone; and (5) spatial configuration around patient bed—relative locations of bed, patient chair, and overbed table, in relation to bathroom door, and resulting obstructions originating from the configuration. Conclusions: Patient falls during unassisted ambulation may be reduced through appropriate examination of these five physical elements/attributes.